INVESTIGATION OF VALUE-SEMANTIC SPHERE OF ENTERPRISES WITH DIFFERENT LEVEL OF PERSONAL RELIABILITY - Lantukh, Igor (PSYCHOLOGICAL JOURNAL, 2018)
The article is devoted to consideration of the problem of development of personal reliability of entrepreneurs. Application of methods: “Personality Questionnaire on Moral and Legal Reliability of the Person” (E.Yu. Strizhov); “Expert Assessment of the Employee’s Personality” (B. G. Bovin); “General Test Ability (GET TEST)”; “Life-Purpose Orientations (LPO)” D.O. Leontiev (modification of “Purpose-in-Life” methodology by J. Krambo, L. Maholik); “Career Anchors” (E. Schein, translated and adapted by V. A. Chiker, V. E. Vinokurova), “Diagnosis of Self-Actualization of Personality” (A. V. Lazukin, adapted by N. F. Kalina) the methodology is adapted version of the Personal Orientation Inventory (POI) by E. Shostrom allowed to investigate the content of the value-semantic sphere of the entrepreneur’s personality with different levels of personal reliability. It was determined the existence of business goals, the degree of satisfaction with the essence of their own life and self-realization, the feeling of having the opportunity to choose their own destiny and to manage it, value orientations in the career and to investigate the indicators of development of personal potential, realization of their own opportunities, degree and direction of self-actualization of entrepreneurs. The author came to the conclusion: Investigation of value orientations in the career among business entities with different level of personal reliability made it possible to determine that the entrepreneurs of group 1 are oriented towards the benefit of people, group 2 have an orientation to integrate the efforts of other people, group 3 consider success to overcome insurmountable obstacles. Application of the sensory-life orientations test allowed to follow the specific features of the semantic sphere of the subjects with different levels of personal reliability. Thus, the investigated of group 1 believe in their own ability to control their lives; the investigated of group 2 are mostly dissatisfied with their lives today, group 3 are contingent with fatalism. Study of indicators of self-actualization of entrepreneurs gave an opportunity to determine the features of value-semantic sphere in the subjects with different levels of personal reliability. Thus, most entrepreneurs of groups 1 and 2 are oriented on personal communication, are not inclined to falsifications or manipulations, do not mix self-disclosure of personality with self-presentation − the strategy and tactics of managing false impressions. Entrepreneurs of group 3 can be described as rigorous. The study will enable in practical sense to optimize the activity of entrepreneurs and make their entry into the European market civilized and well-considered.